2021
DOI: 10.3390/v13061064
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Persistence, and Factors Associated with SARS-CoV-2 IgG Seropositivity in a Large Cohort of Healthcare Workers in a Tertiary Care University Hospital in Northern Italy

Abstract: This observational study evaluated SARS-CoV-2 IgG seroprevalence and related clinical, demographic, and occupational factors among workers at the largest tertiary care University-Hospital of Northwestern Italy and the University of Turin after the first pandemic wave of March–April 2020. Overall, about 10,000 individuals were tested; seropositive subjects were retested after 5 months to evaluate antibodies waning. Among 8769 hospital workers, seroprevalence was 7.6%, without significant differences related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 52 publications
3
26
1
Order By: Relevance
“…The incidence of positives among HCWs in our experience is similar to that found by Lahner et al [ 8 ] and much lower if compared to what was found by Scozzari et al and Fong et al [ 9 , 10 ], testifying the effectiveness of the preventive measures. The percentage of positives among supervised operators is double among nurses compared to doctors (respectively, 4.5% vs. 1.9%), a trend also found in a Chinese study concerning the first months of the pandemic [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of positives among HCWs in our experience is similar to that found by Lahner et al [ 8 ] and much lower if compared to what was found by Scozzari et al and Fong et al [ 9 , 10 ], testifying the effectiveness of the preventive measures. The percentage of positives among supervised operators is double among nurses compared to doctors (respectively, 4.5% vs. 1.9%), a trend also found in a Chinese study concerning the first months of the pandemic [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…In particular, in Italy, the vaccination campaign started at the end of 2020 with the administration of BNT162b2 vaccine (Pfizer/BioNTech) to healthcare personnel and elderly individuals in nursing homes. In 2020, we conducted an observational study on SARS-CoV-2 IgG seroprevalence in relation to clinical, demographic, and occupational factors among health care, administrative, and service personnel, at a large tertiary care university hospital in Turin [ 1 ]. Currently, the dynamics and magnitude of serological response in vaccinated individuals are being monitored in terms of levels and duration of anti-spike IgG antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen new studies reported on the association between exposures and likelihood of infection ( Supplement Table 3 ) ( 6–8 , 11 , 12 , 14 , 16 , 17 , 19 , 20 , 23–25 ). Seven studies ( 7 , 8 , 12 , 19 , 20 , 23 , 24 ) consistently found that exposure to COVID-19 in a household or private setting was associated with increased risk for SARS-CoV-2 infection in HCWs (adjusted odds ratios [ORs] ranged from 2.55 to 8.98) ( Supplement Table 3 ). In most studies, household or private setting exposure was a stronger risk factor than work exposure.…”
mentioning
confidence: 99%